Evolution of Access Routes to High Mountain Refuges of the Mer de Glace Basin (Mont Blanc Massif, France) - Jacques Mourey; Ludovic Ravanel (Revue de Géographie Alpine)
Glacial shrinkage and the gravitational processes associated with it, which are characteristic of global warming effects in high mountain environments, are affecting mountaineering routes more and more, including access routes to high altitude refuges. These changes have almost never been studied. Also, this research seeks to identify and explain the evolution of access trails to five refuges, located in the Mer de Glace basin (Mont Blanc massif), over more than a century. This glacier is the largest in France (L = 11.5 km, SA = 30 km²) is a major Alpine tourist attraction since 1741 and is the birthplace of mountaineering. This work is based on a three-step methodology: 1) collection and analysis of maps, climbing guidebooks and photographs, 2) semi-structured interviews and 3) analysis of high-resolution digital terrain models obtained through terrestrial laser scanning.While there was not a significant evolution during most of the 20th century, glacier thickness loss and the associated erosion of lateral moraines have resulted in numerous modifications made to the access trails since the 1990s. Despite these adaptations, the danger they pose continues to rise, and the necessity to equip them is ever more important (633 m. of ladders at present), which raises doubts about the future accessibility of such high mountain refuges.